Plant diversity and community composition in managed humid coastal dune slacks in NW England. - Margaret A Connor (Public Library of Science (PLoS), 2021)
Humid coastal dune slacks are an endangered habitat in Northwestern Europe. In the UK, dune slacks are currently classified as being in 'unfavourable' condition, with projected decrease in England of up to 30% by 2036. Studies in mainland Europe suggest that regional factors (e.g. slack area, age, and isolation) are more important than local factors (e.g. soil, pH, soil nutrient and water status) in driving successional vegetation processes in coastal slacks. However, this has never been tested for the UK, where approximately 14% of European slacks occur. We used previously established survey protocols to test whether regional factors are more important than local factors in UK coastal slacks, along the Sefton Coast in NW England. We found that slack area and slack age were more important than local factors in driving plant community composition and species richness. We also showed that higher levels of management, such as active grazing and invasive shrub and tree removal, are effective in increasing soil moisture levels in slacks. Our results suggest that similar successional processes are likely to be important in slacks in the NW of England, compared to mainland Europe.